PERILAKU BERFOTO SELFIE SEBAGAI KECENDERUNGAN MUNCULNYA GAYA HIDUP MODERN (Studi tentang Kegiatan Berfoto Selfie pada Mahasiswa di Universitas Riau) - Suci Ananda Harisa; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Selfie becomes world’s trend conducted by various groups ranging from the children to adults. Selfie can be used as a means to fill spare time and become their own entertainment. In fact, most people can feel calm after taking selfie. Selfie also a means to express themselves, for some people. Many people do selfies and upload them to social media for various reasons, such as a hobby, to get the attention and recognition or appreciation for others in social media who see the selfie. This study was conducted to determine how activities and self-concept that shows the emergence of new lifestyle of universitas riau’s students. This study used a qualitative method. The number of informants were five people. Data collection techniques used in this research were observation, interview and documentation. The conclusion is that taking selfie activity is a new trend of modern lifestyle which can be seen from how informants or perpetrators selfie consumptive of quota usage internet data packets, the purchase of support equipment for selfie, or perpetrator selfie aims at being popular at social media.Keywords: selfie, lifestyle trends, social media, self-concept